Enhancing corporate leadership of zakat management and administration in Malaysia: the effect of quality leadership on management and administration of Pusat Pungutan Zakat, Federal Territory Islamic Council - Mhd. Sarif, Suhaimi (2010)
The study examined the effect of quality leadership on the management and administration of Pusat Pungutan Zakat (PPZ) on zakat collection. The study used qualitative (personal interview) and quantitative (survey) and it was conducted within three months. Respondents for the personal interview comprised senior executives of PPZ. The results from the personal interview were used to develop questionnaire. The results from the personal interview indicated that monetary benefits, friendly customer service, good working environment and organizational image are very important factors for an effective leadership. The questionnaire was administered on officers and staff of PPZ, zakat payers and prospective zakat payers. The survey results also confirmed the four factors for effective quality leadership. The study suggests the future research to expand the scope and depth of effective leadership factors and also to include other zakat collection centres in Malaysia.